The Influence of Teacher Readiness and Learning Facilities on Student Learning Motivation: Blended Learning as a Mediating Variable - Mario Parinsi; Yosua Fitsgerald Ratumbuisang; Keith Francis Ratumbuisang (South Sulawesi Education Development (SSED), 2024)
Student learning motivation after the Covid-19 pandemic has become an interesting topic, student learning motivation plays an important role in the learning process. Problems with student learning motivation can arise due to a lack of teacher readiness or lack of support for learning facilities. These factors can hinder students' interest and enthusiasm in the learning process. The aim of this research is to determine the effect of teacher readiness and learning facilities on student learning motivation with blended learning as a mediating variable. The method used in this research is quantitative with an ex-post facto approach. The sample in this research was 12 teachers and 108 students spread across 4 vocational schools in Minahasa. The analysis technique used was Structural Equation Modeling with SmartPLS 3.0 supporting software. The results of this research show that teacher readiness, learning facilities and blended learning have a significant effect on student learning motivation. Blended learning can mediate teacher readiness and learning facilities on student learning motivation. Teacher readiness and learning facilities have an important role in motivating student learning and blended learning is a learning model to increase student learning motivation. Keywords: ; , , Teacher Readiness